Enhancing Museum Brand Awareness through Immersive Technologies: A Case Study for MHNC-UP - Marika Pokhodnia (2024)
Museums foster cultural experiences through their displays and the stories that accompany them. However, in today's digital world, most museums struggle to attract young audiences. In this study, we try to find out how museums are adopting immersive technologies, particularly Virtual Reality (VR), Augmented Reality (AR) and Mixed Reality (MR) and Game Engine (GE) technologies to enhance brand awareness. The study's main goal is to create an augmented reality (AR) enhanced marketing campaign for young adult audiences for the Museum of Natural History and Science of the University of Porto (MHNC-UP) in Portugal. This campaign utilizes interactive posters that engage students with three-dimensional (3D) AR models, offering scientific insights into the museum's exhibits and encouraging further exploration by visiting in person. Through the use of mobile interactive technologies, the campaign aims to increase visitor interaction and awareness for the museum while highlighting the significance of cultural heritage in today's digital age. A total of 167 participants were surveyed, and 4 follow-up interviews were done to gain detailed insights that helped evaluate the campaign's impact. Through the natural history exhibitions at the MHNC-UP Museum, the initiative also supports the knowledge and appreciation of biodiversity and sustainability, which is in line with the UN Sustainable Development Goals.